2012
DOI: 10.7150/ijms.9.47
|View full text |Cite
|
Sign up to set email alerts
|

Oral Infection by Staphylococcus Aureus in Patients Affected by White Sponge Nevus: A Description of Two Cases Occurred in the Same Family

Abstract: Introduction. White Sponge Nevus (WSN) is a rare pathology with a pathogenesis on genetic basis, a benign course and a localization affecting the mucosal keratin.WSN is usually a symptomless pathology: when pain is present, some authors reported reduction of symptoms by taking penicillin or oral tetracycline rinses, suggesting that a bacterial overinfection could be at the base of possible painful symptoms.Case Report. We describe 2 patients affected by WSN, father and son: they presented two different oral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 15 publications
1
45
0
1
Order By: Relevance
“…Similarly to our case, another unusual case of gingival anaplastic large-cell lymphoma mimicking a benign hyperplastic lesion in a 57-year-old man as the first oral clinical manifestation of acquired immunodeficiency syndrome (AIDS) has been reported in the literature [10]. Other benignant oral lesions that might mimic potentially premalignant lesions, for instance, with sponge nevus, require careful clinical and histological examinations, avoiding misdiagnosis [17]. In face of the many potential diagnoses and considering the aggressive behavior of the lesion, the incisional biopsy was performed.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly to our case, another unusual case of gingival anaplastic large-cell lymphoma mimicking a benign hyperplastic lesion in a 57-year-old man as the first oral clinical manifestation of acquired immunodeficiency syndrome (AIDS) has been reported in the literature [10]. Other benignant oral lesions that might mimic potentially premalignant lesions, for instance, with sponge nevus, require careful clinical and histological examinations, avoiding misdiagnosis [17]. In face of the many potential diagnoses and considering the aggressive behavior of the lesion, the incisional biopsy was performed.…”
Section: Discussionsupporting
confidence: 55%
“…About bacterial infection of the oral cavity, it is scientifically confirmed that surface geometry and microarchitecture of materials modified eukaryotic cell adhesion [31] and cariogenic streptococci adhesion [32]. Moreover, the corrugated plaques together with the altered texture of the mucosa create the right conditions for the colonization and the development of microbial species such as saprophytic bacteria or fungal species [33]. The development of novel biomaterial coatings or scaffolds that enhance early osseointegration yet deters the attachment of bacteria are especially desirable properties to avoid aseptic and septic loosening.…”
Section: Discussionmentioning
confidence: 97%
“…16,17 This anatomical and functional deficiency dramatically impair the PH level in preterm children oral cavity, affecting negatively the enamel structure and the efficacy of saliva to contrast common oral infections. 18 These salivary and PH alterations may be able to create an altered oral environment, leading to a development of atypically aggressive dental pathologies. 19 Our results confirmed the association between GER and preterm birth, as well as GER and breastfeeding: in the light of what literature have showed about the damages related to untreated GER in paediatric patients, we solicit a special attention when dentists perform the anamnesis and the first visit to factors as the long-time breastfeeding and the preterm birth.…”
Section: Discussionmentioning
confidence: 99%